Pengaruh Pemanfaatan Limbah Batu Onyx sebagai Subtitusi Agregat Kasar Terhadap Beton Porus - Utomo, Rendy Cahyo; Rochmah, Nurul (Jurnal Sains dan Teknologi (JSIT), 2026)
Conventional concrete, which is impermeable in nature, can increase surface runoff and cause water ponding problems. Therefore, an alternative construction material that supports better drainage systems is required. One potential solution is porous concrete utilizing waste onyx stone as a partial replacement for coarse aggregate.This study aims to analyze the effect of using waste onyx stone as a substitute for coarse aggregate on the compressive strength and permeability of porous concrete.The research method used was a laboratory experimental method with variations of waste onyx stone substitution of 0%, 50%, 75%, and 100% of the total coarse aggregate. The tests conducted included material characteristic testing, compressive strength testing at 7 and 28 days, and permeability testing of porous concrete.The results showed that the use of waste onyx stone affected the compressive strength and permeability of porous concrete. At 7 days, the 0% variation produced the highest compressive strength of 5.91 MPa, while the 100% variation produced the lowest value of 4.25 MPa. At 28 days, the highest compressive strength was obtained in the 0% variation at 10.35 MPa, while the lowest was in the 100% variation at 4.62 MPa. The permeability test results showed an increase from 0.36 cm/s in the 0% variation to 0.60 cm/s in the 100% variation. The higher the substitution of waste onyx stone, the higher the permeability value, while the compressive strength tended to decrease.